Catalyst support made from porous local clay-fly ash composites fof activated carbon materials\ - Chan, Wai Hoong (School of Materials Engineering, 2016)
Currently, the fabrication of porous ceramic composites is still at developmental stage in Malaysia. Thus, this research has focused on the development of porous ceramics composites via polymer sponge replica technique along with the utilisation of clay and fly ash obtained in Malaysia. On the other hand, this research is divided into four sections. The first section is the testing and characterisations of the received raw materials. The second section is the mixture between clay and fly ash in a suitable mixing ratio to produce clay-fly ash composite. The composite mixture is impregnated in a reticulated structure template to form porous ceramic composites. The third section involves the extracted carbon from fly ash and sucrose as the carbon precursors. These carbon precursors are used to form a carbon coating layer on the surface of porous clay-fly ash composites. Finally, the fourth section is the activation of carbon coating layer with the assistance of chemical activating agent and microwave energy. The summary of the research works is schematically shown in Fig. 1.2.